2014
DOI: 10.1016/j.celrep.2014.10.042
|View full text |Cite
|
Sign up to set email alerts
|

An Active Role for the Ribosome in Determining the Fate of Oxidized mRNA

Abstract: SUMMARY Chemical damage to RNA affects its functional properties and hence may pose a significant hurdle to the translational apparatus; however, the effects of damaged mRNA on the speed and accuracy of the decoding process and their interplay with quality control processes are not known. Here, we systematically explore the effects of oxidative damage on the decoding process using a well-defined bacterial in vitro translation system. We find that the oxidative lesion 8-oxoguanosine reduces the rate of peptide-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
202
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(210 citation statements)
references
References 40 publications
7
202
0
1
Order By: Relevance
“…This finding, together with the finding that the kinetics of tRNA decay upon amino acid starvation are similar in wild-type E. coli and a relA mutant, suggests that tRNA instability is not a unique consequence of the stringent response, but may occur as a general response to stresses that reduce translation. 14 The argument is supported by a recent report of extensive tRNA degradation during oxidative stress, 30 which causes stalling of ribosomes at 8-oxoG residues in the mRNA 31 and thereby also limits the pool of functionally intact mRNA available for translation. Since the capacity to synthesize new protein is severely reduced during amino acid starvation, a tRNA-degradation mechanism that depends on synthesis of new protein may not be feasible.…”
Section: A Demand-based Model For Trna Degradationmentioning
confidence: 94%
“…This finding, together with the finding that the kinetics of tRNA decay upon amino acid starvation are similar in wild-type E. coli and a relA mutant, suggests that tRNA instability is not a unique consequence of the stringent response, but may occur as a general response to stresses that reduce translation. 14 The argument is supported by a recent report of extensive tRNA degradation during oxidative stress, 30 which causes stalling of ribosomes at 8-oxoG residues in the mRNA 31 and thereby also limits the pool of functionally intact mRNA available for translation. Since the capacity to synthesize new protein is severely reduced during amino acid starvation, a tRNA-degradation mechanism that depends on synthesis of new protein may not be feasible.…”
Section: A Demand-based Model For Trna Degradationmentioning
confidence: 94%
“…Whatever the mechanism, it is clear that m 6 G at the second position slows translation at least 1000-fold. Such a strong roadblock would likely engage the ribosomal rescue pathways (tmRNA in bacteria and No-Go Decay in eukaryotes) (Doma and Parker 2006;Moore and Sauer 2007;Tsuboi et al 2012) as we have observed recently for mRNAs containing the oxidation adduct 8-oxo-G (Simms et al 2014). Further study will be necessary to delineate how m 6 G at the second position stalls translation and to assess what effect this would have on cellular fitness.…”
Section: Discussionmentioning
confidence: 99%
“…Dipeptide products were then resolved by electrophoretic TLC and the overall efficiency of peptide-bond formation assessed by quantifying the amount of dipeptide products relative to unreacted fMet (Youngman et al 2004). This approach has been recently used by our laboratory to monitor the efficiency of incorporation of every single amino acid and, importantly, recapitulates to a large extent the level of fidelity measured in vivo (Simms et al 2014).…”
Section: Effects Of Mmentioning
confidence: 99%
See 2 more Smart Citations